2020
DOI: 10.3892/ol.2020.11415
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary treatment system for bone metastases for early diagnosis, treatment and prevention of malignant spinal cord compression

Abstract: Malignant spinal cord compression (MSCC) is a serious complication of cancers. The present study aimed to establish a multidisciplinary treatment system for urgent magnetic resonance imaging (MRI) and referral to orthopedists in order to prevent neurological deficits caused by MSCC. In the present study, the extent to which this system achieved early diagnosis and treatment and prevented MSCC-caused neurological deficits was examined. The records from patients with neurological deficits caused by MSCC before (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…This tool was developed by the researcher based on review of relevant literature (50) to assess the actual nursing care provided for patients with Metastatic spinal cord compression (MSCC) before and after implementation of the Educational program.…”
Section: Checklistmentioning
confidence: 99%
“…This tool was developed by the researcher based on review of relevant literature (50) to assess the actual nursing care provided for patients with Metastatic spinal cord compression (MSCC) before and after implementation of the Educational program.…”
Section: Checklistmentioning
confidence: 99%
“…Nakata examined the usefulness of a rapid referral system to provide urgent access to MRI scanning, referral to orthopedists, and administration of RT for the urgent management of neurological deficits caused by metastatic spinal cord compression. As a result, the use of the system significantly improved the incidence and severity of neurological deficits following treatment [ 21 ]. For the effects of rehabilitation, Rief et al have shown that guided isometric training of the paravertebral muscles can be safely practiced in palliative patients with stable bone metastases of the vertebral column, improving their pain score and mobility [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous articles have called for a multidisciplinary approach to bone metastasis (3)(4)(5)(6)(7)(8)(9)(10)(11). However, most of them did not shed light on the statistical validity.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not demonstrate clinical efficacy (6). Nakata et al evaluated 45 patients with bone metastasis to the spine with paralysis, and only revealed the clinical efficacy of the multidisciplinary approach (11). They reported that the cancer board shortened the time to diagnosis and treatment, besides reducing the incidence of paralysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation